(untitled) (Research, Society and Development, 2022)
Liver cancer is called the fifth most incident type of neoplasm and fourth with prominence in the causes of death worldwide, within this branch the hepatocellular carcinoma stands out, being mostly asymptomatic. From this, active methodologies are extremely relevant during learning in health courses. Therefore, the objective of this work was to approach an experience report of the performance of a multidisciplinary team of undergraduates in the health area in the resolution of a fictitious clinical case about a patient with hepatocellular carcinoma using an active methodology. The experience of the activities took place in September 2021 during a theoretical class in which the resolution of a contextualized clinical case was proposed for the formulation of a multidisciplinary therapeutic plan. In view of this, it was possible to design a unique multiprofessional therapeutic plan, making the appropriate choice of treatment according to the clinical case in question, highlighting the contribution of active methodologies in the training of undergraduates in the health area. In short, such methods are of great value in amplifying knowledge about the subject in question, thus appropriating the teaching-learning axis within oncology, in addition to encouraging critical and reflective thinking in undergraduates.